Cinema Africa 24/25: A Conversation with Mohamed Kordofani, director of "Goodbye Julia" (Cinema Africa 2024/25, 2025)
Mohamed Kordofani's critically acclaimed movie "Goodbye Julia" is his first feature film. As part of the 16th edition of Cinema Africa Kordofani came to Bayreuth to present his film to the Bayreuth public. Maryam Shojaei and Bakheit Nur had the chance to sit down with him and ask him a few questions on his career, his film and the political background that frames this extraordinary work of art.